STRENGTHENING BHINNEKA TUNGGAL IKA AS AN IDENTITY AND UNIFIER OF THE NATION: REALIZING A PEACEFUL ISLAM AND STATEHOOD HARMONIZATION - Baihaki, Egi Sukma (ADDIN, 2017)
The development of the word and the rise of acts such as the destruction of worship houses disputes between religious communities and the acts of terrorism can harm the social order that has been well tied by Bhinneka Tunggal Ika. Thus, understanding about “Bhinneka Tunggal Ika” is an important thing to be concerned and maintained by all elements of the nation. Because the diversity that has existed in Indonesia is a noble heritage deposited by the predecessors to be continued and maintained. Strengthening Bhinneka Tunggal Ika will be needed to reinforce the identity of Indonesia, and become a unifying media for any different faction to unite and to create the peaceful, secure, and prosperous life.